Miles to go (mtgo) encodes FNDC3 proteins that interact with the chaperonin subunit CCT3 and are required for NMJ branching and growth in Drosophila. - Syed, A.; Lukacsovich, T.; Pomeroy, M.; Bardwell, A.J.; Decker, G.T.; Waymire, K.G.; Purcell, J.; Huang, W.; Gui, J.; Padilla, E.M.; Park, C.; Paul, A.; et al. (Developmental Biology, 2019)
Analysis of mutants that affect formation and function of the Drosophila larval neuromuscular junction (NMJ) has provided valuable insight into genes required for neuronal branching and synaptic growth. We report that NMJ development in Drosophila requires both the Drosophila ortholog of FNDC3 genes; CG42389 (herein referred to as miles to go; mtgo), and CCT3, which encodes a chaperonin complex subunit. Loss of mtgo function causes late pupal lethality with most animals unable to escape the pupal case, while rare escapers exhibit an ataxic gait and reduced lifespan. NMJs in mtgo mutant larvae have dramatically reduced branching and growth and fewer synaptic boutons compared with control animals. Mutant larvae show normal locomotion but display an abnormal self-righting response and chemosensory deficits that suggest additional functions of mtgo within the nervous system. The pharate lethality in mtgo mutants can be rescued by both low-level pan- and neuronal-, but not muscle-specific expression of a mtgo transgene, supporting a neuronal-intrinsic requirement for mtgo in NMJ development. Mtgo encodes three similar proteins whose domain structure is most closely related to the vertebrate intracellular cytosolic membrane-anchored fibronectin type-III domain-containing protein 3 (FNDC3) protein family. Mtgo physically and genetically interacts with Drosophila CCT3, which encodes a subunit of the TRiC/CCT chaperonin complex required for maturation of actin, tubulin and other substrates. Drosophila larvae heterozygous for a mutation in CCT3 that reduces binding between CCT3 and MTGO also show abnormal NMJ development similar to that observed in mtgo null mutants. Hence, the intracellular FNDC3-ortholog MTGO and CCT3 can form a macromolecular complex, and are both required for NMJ development in Drosophila.